2022
DOI: 10.1088/1475-7516/2022/01/056
|View full text |Cite
|
Sign up to set email alerts
|

On the duality of massive Kalb-Ramond and Proca fields

Abstract: We compare the massive Kalb-Ramond and Proca fields with a quartic self-interaction and show that the same strong coupling scale is present in both theories. In the Proca theory, the longitudinal mode enters the strongly coupled regime beyond this scale, while the two transverse modes propagate further and survive in the massless limit. In contrast, in case of the massive Kalb-Ramond field, the two transverse modes become strongly coupled beyond the Vainshtein scale, while the pseudo-scalar mode remains in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Additionally, this field could be the source of spontaneous Lorentz Symmetry Breaking (LSB), if self-interaction potential and non-vanishing vacuum expectation value (VEV) are assumed [22]. In the pioneering work [23] it was shown that KR field could be dual to the massive spin-1 field, namely Proca field. This property could be used in the study of exotic Proca, Boson-Proca stars.…”
Section: B Kalb-ramond Field and The Rise Of Bouncing Cosmologymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this field could be the source of spontaneous Lorentz Symmetry Breaking (LSB), if self-interaction potential and non-vanishing vacuum expectation value (VEV) are assumed [22]. In the pioneering work [23] it was shown that KR field could be dual to the massive spin-1 field, namely Proca field. This property could be used in the study of exotic Proca, Boson-Proca stars.…”
Section: B Kalb-ramond Field and The Rise Of Bouncing Cosmologymentioning
confidence: 99%
“…Moreover, massless KR field could occur in the critical and massless string spectrum due to the compactification to four dimensions [21]. Additionally, this field could be the source of spontaneous Lorentz Symmetry Breaking (LSB) if self-interaction potential and non-vanishing vacuum expectation value (VEV) are assumed [22]. In a pioneering study [23], it was shown that the KR field could be dual to the massive spin-1 field, namely the Proca field.…”
Section: B Kalb-ramond Field and The Rise Of Bouncing Cosmologymentioning
confidence: 99%